Influence of processing methods on the content of polyphenols and anthocyanins and on the antioxidant activity of Rubus brasiliensis Mart. fruits - Ana Paula Anzolin; Charise Dallazem Bertol; Gian Carlos Taparello; Verônica Cristina da Silveira; Pâmela do Nascimento; Luciana Grazziotin Rossato-Grando (Brazilian Journal of Food Technology, 2022)
Abstract Little is known about the phytochemical composition and the influence of different processing methods on the concentration of bioactive compounds and on the antioxidant activity of the fruits of Rubus brasiliensis Mart., a native plant of Brazil. This work aimed to evaluate the influence of different processing methods on the quantification of phenolic and anthocyanin compounds and on the antioxidant activity of R. brasiliensis fruits. The plants were processed by different ways - the extracts of fruits were obtained by Spray Dryer (SD) or Lyophilization (LYO), and the fruits were dried directly in an oven (OD) and were also evaluated after freshly thawed (FT). The processing methods were independent. After processing, the polyphenol and anthocyanin contents and antioxidant activity were evaluated. The Total Phenolic Content (TPC) was assessed using the Folin-Ciocalteu technique. The pH differential method was used for quantification of anthocyanin and the antioxidant activity was determined by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. R. brasiliensis fruits have a high content of polyphenols and anthocyanins, and an expressive antioxidant activity that can bring benefits to the population. The FT fruits showed the lowest content of total polyphenols. However, the OD fruits showed the most interesting results, since the total polyphenols and anthocyanins contents and the antioxidant activity were similar to the other processing methods performed in this work and were more economically viable. Obtain a bioactive content and adequate antioxidant activity after simple processing such as drying is very interesting when using these fruits for longer, or even, obtaining pharmaceutical formulations. It could be determined, for the first time, the content of polyphenols and anthocyanins and the antioxidant activity of the fruits of R. brasiliensis, as well as the best way to process these fruits by drying them in an oven.